PERSEPSI MASYARAKAT KOTA BENGKULU TERHADAP PAHAM ISLAM MODERAT - Wahyu Abdul Jafar (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2018)
This research was conducted to describe the perception of resident of Bengkulu about moderate Islamic understanding. In collecting the research data, researchers used purposive sampling technique. While the data collection techniques used are interviews and documentation. From the research in the field, important conclusions were obtained namely, resident of bengkulu has some perception about moderate Islamic understanding, among others: first, Moderate Islamic understanding is the teachings of Islam that is tasamuh (tolerant), tawazun (balanced), i'tidal (straight) and tawasuth (mediocre). Secondly, Moderate Islamism is the Islamic teaching that is Rahmatan Lil Alamin. Thirdly, moderate Islamic understanding is a humanist teaching, humanistic, gentle, polite, not anarchic and peace-loving. Fourthly, Moderate Islamism is an Islamic teaching that opens itself with progress and in harmony with the concept of Indonesian statehood. Fifth, Moderate Islamism is the Islamic teachings of Islam that prioritize the value of the unity and integrity of the nation and the state. Sixth, Moderate Islamism is the teachings of Islam which emphasizes the amar ma'rufnya side of the nahi mungkarnya side. Seventh, Moderate Islamism is a strictly Islamic teaching for the afterlife and flexible for world affairs. Eighth, Moderate Islamism is a liberal and perverted teaching of Islam. Ninth, Moderate Islamism is an Islamic teaching that is heretical and weakens the Islamic ummah. Tenth, Islamic understanding Moderet is the Islamic teaching that is a mirage and divide the Muslims.